MARKETING AND MANAGEMENT UNDER CURRENT CONDITIONS IN UKRAINE: NOOSPHERIC ASPECT OF DEVELOPMENT - Chernov S.I. (Pressing Problems of Public Administration, 2017)
The paper considers the phenomena of marketing and management from the perspective of the regional noospheric development theory and its advantages over the theory of sustainable development. The author presents his vision of the processes of forming and implementing a marketing policy in the context of regional noospheric development and use of the socio-cultural potential of public management under the current conditions of state administration modernizing in the line of public administration and information society advancement.